Computational study of the mixed B-site perovskite SmBxCo1−xO3−d (B = Mn, Fe, Ni, Cu) for next generation solid oxide fuel cell cathodes. Issue 18 (18th April 2019) - Olsson, Emilia; Cottom, Jonathon; Aparicio-Anglès, Xavier; de Leeuw, Nora H.
Abstract : The effect of Co-site doping on the electronic, magnetic, and physical properties of next-generation SOFC cathode SmCoO3 . Abstract : SmCoO3 is a promising perovskite material for the next generation of intermediate temperature solid oxide fuel cells (SOFC), but its potential application is directly linked to, and dependent on, the presence of dopant ions. Doping on the Co-site is suggested to improve the catalytic and electronic properties of this cathode material. Fe, Mn, Ni, and Cu have been proposed as possible dopants and experimental studies have investigated and confirmed the potential of these materials. Here we present a systematic DFT+ U study focused on the changes in electronic, magnetic, and physical properties with B-site doping of SmCoO3 to allow cathode optimization. It is shown that doping generally leads to distortion in the system, thereby inducing different electron occupations of the Co d-orbitals, altering the electronic and magnetic structure. From these calculations, the 0 K electronic conductivity ( σ e ) was obtained, with SmMn x Co1− x O3 having the highest σ e, and SmFe x Co1− x O3 the lowest σ e, in agreement with experiment. We have also investigated the impact of dopant species and concentration on the oxygen vacancy formation energy ( E f ), which is related to the ionic conductivity ( σ O ). We found that the E f values are lowered only when SmCoO3 is doped with Cu or Ni. Finally, thermal expansion coefficients were calculated, with Mn-doping showing the largest decrease at low x and at x = 0.75. Combining these results, it is clear that Mn-doping in the range x = 0.125–0.25 would imbue SmCoO3 with the most favorable properties for IT-SOFC cathode applications.